Asymmetric Synthesis and Antitumor Activity of Spiro‐Oxadiazole Derivatives from 1, 4:3, 6‐Dianhydro‐D‐fructose. Issue 9 (29th June 2017) - Xu, Wenke; Ge, Yongxun; Hou, Yu; Liu, Yingju; Hua, Yingchun; Han, Weiwei; Qin, Zhiyan; Liu, Fengwu
Abstract : A series of spiro‐oxadiazoles were synthesized from 1, 4:3, 6‐dianhydro‐ D ‐fructose and hydrazides via a stereo‐ selective two‐step reaction sequence. The structures of newly synthesized compounds were established by spectral analysis. The absolute configuration of compound2a was further confirmed by single crystal X‐ray analysis. All the synthesized compounds were screened for their in vitro antitumor activity, showing that these compounds have poor inhibitory activities against A549, MGC‐803 tumor cells. Abstract : A series of spiro‐oxadiazoles were synthesized from 1, 4:3, 6‐dianhydro‐ D ‐fructose and hydrazides via a stereo‐selective two‐step reaction sequence. The structures of the newly synthesized compounds were established by spectral analysis. The absolute configuration of compound2a was further confirmed by single crystal X‐ray analysis. All the synthesized compounds were screened for their in vitro antitumor activity, showing that these compounds have poor inhibitory activity against A549, MGC‐803 tumor cells.